Legislative provision of access to higher education for the disabled students in European countries. - Городецька, Юлія Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the given the author analyzes the legislative base of the European states in the field of highereducation availability for the disabled. The directions of educational services granting for the disabledstudents are determine according to the normative documents.